Ethnological approach to acorn utilization in prehistory: A case study of acorn mook making in South Korea - An, Ting; Tang, Mengxia; An, Juhui (Frontiers in Plant Science, 2022)
Acorn remains are reported from prehistoric sites across the world. Acorn is argued to have been an important food resource for human beings in prehistory. However, relevant research is still limited and it is often difficult to recognize archaeological remains relating to acorn utilization. The Chaîne Opératoire of acorn utilization is yet to be addressed. Such is of great significance to the study of human subsistence strategy in pre-agricultural period and moreover the origin of agriculture. By conducting a case study of 'mook making' using acorns in Yongdong-gun, Chungcheongbuk-do, South Korea, the current paper explores the Chaîne Opératoire of acorn utilization in prehistory using an ethnological approach. We draw attention to the laborious nature of acorn processing and to different methods of acorn processing due to different species and culinary tradition. Our case study also brings new insights into archaeological interpretations of acorn remains from prehistorian sites.